Motivating your R&D staff - Manners, George E. Jr (Research management (Now: research technology management))
George E. Manners, Jr., Joseph A. Steger and Thomas W. Zimmerer, in their RTM Classic, present the basics for generating the excitement they consider the essence of motivation for technical people.